Study on Ill Effects Caused by Air Pollutants on People at Cement Manufacturing Unit - S, Dhinu priya; G, Poovizhi; D, Ambika (International Research Journal of Multidisciplinary Technovation, 2019)
The cement industry is one of the most polluting industries in the world. It is responsible for emission of pollutants such as particulate matter, carbon dioxide, carbon monoxide, sulphur oxide and nitrogen oxide. It adversely affects the environment and health of the people. It is emitted by burning of pet coke and is higher in concentration due to coalmine wastes and scrap tires. The health effects on people are eye and skin irritation, head ache, respiratory problems, cardio vascular problems and cancer. It also affects pregnant woman which have negative effects such as low birth weight, defects in respiratory system, asthma and allergies. In this paper, the effect of air pollutants from cement manufacturing unit is studied. The areas around cement industry are identified and survey by direct observation is conducted. The pollutants and effects are listed from the observation. The impacts of air pollution on people and their awareness on air pollution are observed. The remedies are suggested to reduce impact on humans.